Contribution to the Astragalus sect. Aegacantha from Pakistan, with the description of a new species and a new record - Khan, Amjad; Sultan, Amir; Mumtaz, Abdul Samad; Bagheri, Ali; Khan, Nazar; Khan, Tahir (Phytotaxa, 2025)
Interesting species with characteristic features of the section Aegacantha were collected from Pakistan, one new species and one new record are described and reported. Astragalus saifullahaicus sp. nov. is close to A. hostilis, but differs from the latter by longer internodes, broadly- triangular stipules, elliptic to obovate leaflets with cuneate base, obtuse apex, often mucronate, racemes 2-flowered and legumes oblong to elliptic, densely covered with appressed hairs and a slightly curved, 3–5.5 mm long beak. Taxonomic descriptions, distribution map, anatomy, palynology, seed micromorphology and IUCN threat category of newly described species are presented. Astragalus nigrocalyx is reported as a new record for flora of Pakistan.